Maintaining Plurality Through the Preservation of the Siulak Kerinci Tradition - Relly Anjar Vinata Wisnu Saputra (Universitas Syiah Kuala, 2023)
This study aims to describe and identify inter-ethnic relations and form existing traditions as a means of inter-ethnic bonding that is able to unite within the frame of brotherhood. The background of this research is the diversity of the Siulak Kerinci community which consists of various ethnicities with a diversity of traditions and their uniqueness. This research is a qualitative research with an ethnographic approach. In the process of data, researchers used the method of observation, interviews and literature study, then the data were analyzed by means of descriptive qualitative. Based on the research, it was found that Siulak Kerinci was inhabited by various ethnic groups, both natives and immigrants. Each ethnic group has its own diversity and uniqueness, including the kenduri sko tradition, the tale tradition and the asyeik dance tradition. These traditions become a unifying tool that is able to unite the various ethnic groups that exist only because ethnicity is only carried out by the participating ethnic groups. There is no longer a dividing line because of the awareness that the existing traditions are national cultural treasures that need to be preserved and maintained. The principle of mutual respect is the main asset in the framework of Bhinneka Tunggal Ika.